Victor Serenus: A Story of the Pauline Era - Wood, Henry, 1834-1909 (Salt Lake City, UT : Project Gutenberg, 2017)
"Victor Serenus: A Story of the Pauline Era" by Henry Wood is a historical novel written in the late 19th century. The narrative is set during the early years of the Christian era and focuses on the character of Saulus Paulus (later known as Paul the Apostle), exploring his upbringing in Tarsus amidst a rich tapestry of cultural and religious conflict. The author aims to blend historical fact with fictional elements, illuminating the spiritual and societal dynamics of the time. At the start of the story, we are introduced to a solemn religious procession in Tarsus, where a group of Hebrew priests leads a ceremonial event. The infant, Saulus Paulus, is presented in a synagogue ritual that underscores his significance within the Jewish community. The tale unfolds against the backdrop of Tarsus, a bustling hub of commerce and culture, characterized by both Hellenistic and Roman influences. As the narrative progresses, it touches on the tensions between the Jewish tradition and the broader pagan society, with predictions about Saulus's future painted vividly through prophetic blessings and hints of his eventual role in the rise of Christianity. This opening segment sets a rich scene, hinting at the larger themes of faith, destiny, and societal conflict that will likely unfold throughout the novel. (This is an automatically generated summary.)
Release date is 2017-07-30
Keywords: Paul, the Apostle, Saint -- Fiction